2020
DOI: 10.1073/pnas.1904532117
|View full text |Cite
|
Sign up to set email alerts
|

Signaling mechanisms of growth hormone-releasing hormone receptor in LPS-induced acute ocular inflammation

Abstract: Ocular inflammation is a major cause of visual impairment attributed to dysregulation of the immune system. Previously, we have shown that the receptor for growth-hormone–releasing hormone (GHRH-R) affects multiple inflammatory processes. To clarify the pathological roles of GHRH-R in acute ocular inflammation, we investigated the inflammatory cascades mediated by this receptor. In human ciliary epithelial cells, the NF-κB subunit p65 was phosphorylated in response to stimulation with lipopolysaccharide (LPS),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 39 publications
2
23
0
Order By: Relevance
“…The involvement of the somatotropic axis in inflammatory states is well known 32 , 33 . Various agonist and antagonist analogs of GHRH have shown marked antinflammatory effects 16 , 19 , 27 , 34 36 . In particular, MIA-690 inhibited inflammation by reducing the production of inflammatory markers in carrageenan-induced chronic prostatitis 35 .…”
Section: Discussionmentioning
confidence: 99%
“…The involvement of the somatotropic axis in inflammatory states is well known 32 , 33 . Various agonist and antagonist analogs of GHRH have shown marked antinflammatory effects 16 , 19 , 27 , 34 36 . In particular, MIA-690 inhibited inflammation by reducing the production of inflammatory markers in carrageenan-induced chronic prostatitis 35 .…”
Section: Discussionmentioning
confidence: 99%
“…Another research showed that LPS stimulated the expression of NF- κ B subunit p65 in human ciliary epithelial cells, resulting in the activation of receptor for growth-hormone-releasing hormone (GHRH-R). The downstream JAK2 is phosphorylated and augments the production of proinflammatory factors [ 43 ]. Therefore, we speculate that JAK2 is likely to be a downstream molecular target of CatB/NF- κ B in the macrophage-mediated inflammatory reaction induced by P. gingivalis .…”
Section: Discussionmentioning
confidence: 99%
“…Uveitis is a general term describing a group of intraocular inflammatory diseases that often affect the uvea [8]. Injection of LPS can generate PAMP-induced uveitis, which is widely used as an animal model to examine the pathological mechanisms of uveitis and ophthalmic inflammation in animals [9][10][11]. In a state of inflammation, the uveal tract, including the iris, shows the accumulation of inflammatory cells.…”
Section: Introductionmentioning
confidence: 99%